علاقة تشكل هوية الأنا بالاغتراب النفسي لدى طلاب الجامعة - تواتي إبراهيم, عيسى (جامعة الوادي - University of Eloued, 2017)
هدفت الدراسة الحالية إلى بحث العلاقة المحتملة بين تشكل هوية الأنا والشعور بالاغتراب النفسي لدى طلاب جامعة الوادي، كما سعت أيضا لمعرفة الفروق في درجة الشعور بالاغتراب النفسي تبعا لمتغير الجنس. من أجل تحقيق ذلك، استخدم في الدراسة مقياس تشكل هوية الأنا للغامدي و مقياس الاغتراب لسميرة أبكر، حيث تم تطبيق هذه الأدوات على عينة قوامها 287 طالبا و طالبة من كلية العلوم الإنسانية و الاجتماعية بجامعة الوادي. و توصلت إلى النتائج التالية: - وجود علاقة ارتباطيه ذات دلالة إحصائية سالبة بين درجات تحقيق هوية الأنا في مجالاتها المختلفة (الأيديولوجية، الاجتماعية، و الكلية) و الشعور بالاغتراب النفسي. - وجود علاقة ارتباطيه ذات دلالة إحصائية موجبة بين درجات رتب الهوية (تعليق، انغلاق، تشتت) في مجالاتها المختلفة (الأيديولوجية، الاجتماعية، و الكلية) و الشعور بالاغتراب النفسي، باستثناء رتبة تعليق الهوية في المجال الاجتماعي فلم تحقق أي علاقة ارتباطية ذات دلالة إحصائية مع الاغتراب النفسي. - وجود فروق ذات دلالة إحصائية في الشعور بالاغتراب النفسي حسب متغير الجنس لصالح الذكور The present study aimed to examine the potential relationship between ego identity and the feeling of psychological alienation among students of El Oued university. It seeks also to recognize the differences in the feeling of psychological alienation according to the variable of gender. For this reason, the study relied on two measures: the objective measure of ego identity standardized by Al Ghamdi and the alienation measure developed by Samira Abker. Then, they were implemented on a sample of 287 male and female students from the Faculty of Humanities and Social Sciences at the University of El Oued. The study resulted in the following findings: - There was a negative and statistically significant relationship between the scores of identity achievement in its different fields (ideological, interpersonal, total) and the feeling of psychological alienation. - There was a positive and statistically significant relationship between the scores of identity statuses (moratorium, foreclosure, diffusion) in its different fields (ideological, interpersonal, and total) and the feeling of psychological alienation, except the moratorium identity status in the interpersonal field which did not reach a statistically significant correlation with psychological alienation. There were statistically significant differences in the feeling of psychological alienation depending on gender variable in favor of males
دراسة ميدانية على عينة من طلبة جامعة الوادي
مقال في مجلة السراج في التربية وقضايا المجتمع بجامعة الوادي
Keywords: هوية الأنا، الاغتراب النفسي، تشكل الهوية، رتب الهوية. طلاب الجامعة; ego identity, psychological alienation, formation of ego, identity statuses. university students